Trust: How It Affects the Use of Telemedicine in Improving Access to Assistive Technology to Enhance Healthcare Services - Bahari G; Mutambik I; Almuqrin A; Alharbi ZH (Dove Medical Press, 2024)
Ghareeb Bahari,1 Ibrahim Mutambik,2 Abdullah Almuqrin,2 Zahyah H Alharbi3 1Nursing Administration and Education Department, College of Nursing, King Saud University, Riyadh, Saudi Arabia; 2Department of Information Science, College of Humanities and Social Sciences, King Saud University, Riyadh, Saudi Arabia; 3Department of Management Information Systems, College of Business Administration, King Saud University, Riyadh, Saudi ArabiaCorrespondence: Ibrahim Mutambik, Email imutambik@ksu.edu.saBackground: Modern telemedicine (TM) technologies play a crucial role in enhancing access to Assistive Technology in healthcare services. However, the full benefits of this technology will not be realized unless it is widely accepted among service users (patients). This study aimed to investigate the impact of patient trust and perceived risk on the acceptance of TM for Assistive Technology in healthcare.Materials and Methods: A comprehensive survey instrument was developed and refined through expert feedback and a pilot study, leading to data collection from 917 participants. The theoretical framework guiding this research was based on the Trust factors in TM, which helped in conceptualizing the factors influencing patient acceptance of TM.Results: The study revealed a significant gap in patient trust in TM and highlighted the multifaceted nature of perceived risk, emphasizing the need to consider individual risk factors separately. Results also indicated that trust in technological reliability and the perceived effectiveness of TM were critical factors influencing its adoption. The findings underscore the importance of building trust among service users and promoting the reliability of TM for achieving desirable medical outcomes.Conclusion: In conclusion, to facilitate widespread acceptance of TM for Assistive Technology, a multi-faceted approach involving healthcare providers, organizations, and governments is essential to address patient concerns, enhance trust, and promote the benefits of this technology.Keywords: trust, risk, telemedicine, TM, technology adoption, patient, behaviour